1994
DOI: 10.3354/dao019233
|View full text |Cite
|
Sign up to set email alerts
|

Mortalities in red claw crayfish Cherax quadncannatus associated with systemic Vibrio mimicus infection

Abstract: Two cases of lnortalities in cultured red claw Materials and methods. Since 1989, sick or dead red crayfish Cherax quadricarinatus associated with systemic Vibno mimicus infections are described. In these cases, V rnirnicus appears to have been an opportunistic pathogen following stress caused by either overcrowding or mismanagement and poor water quality. Humans consuming raw or improperly cooked infected crayfish could be at risk of contracting gastrointestinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Some species of bacteria are known to be pathogens of stressed freshwater crayfish. For example, Vibrio mimicus has been associated with mortality in highly stressed freshwater crayfish in USA (THUNE et al, 1991) and Australia (EAVES and KETTERER, 1994). Based on published data, there is no reported exotic Gram negative or Gram-positive bacterium which obviously represents a serious threat to European freshwater crayfish.…”
Section: Bacteriamentioning
confidence: 99%
“…Some species of bacteria are known to be pathogens of stressed freshwater crayfish. For example, Vibrio mimicus has been associated with mortality in highly stressed freshwater crayfish in USA (THUNE et al, 1991) and Australia (EAVES and KETTERER, 1994). Based on published data, there is no reported exotic Gram negative or Gram-positive bacterium which obviously represents a serious threat to European freshwater crayfish.…”
Section: Bacteriamentioning
confidence: 99%
“…Mass mortalities in pond-reared redclaw have so far been caused by bacterial diseases including vibriosis (Eaves & Ketterer 1994) and those due to infections with rickettsiales-like organisms (Ketterer et al 1992).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Sub-clinical viral infections have been reported (Edgerton et al 1994, Edgerton & Owens 1999, but crayfish with these infections have usually been coinfected with bacterial and/or other pathogens. Mass mortalities in pond-reared redclaw have so far been caused by bacterial diseases including vibriosis (Eaves & Ketterer 1994) and those due to infections with rickettsiales-like organisms (Ketterer et al 1992).…”
Section: Several Viruses Have Been Described From Farmedmentioning
confidence: 99%
“…A number of viruses (Anderson & Prior 1992, Edgerton et al 1994, 1995 'Corresponding author. E-mail: leigh.owens@jcu.edu.au Owens & McElnea 2000), bacteria (Ketterer et al 1992, Owens et al 1992, Eaves & Ketterer 1994, Webster 1995 and ectoparasites (Herbert 1987(Herbert , 1988 have been reported in Australia, and the presence of Cherax bacilliform virus (Groff et al 1993) and rickettsiae (Jimenez & Romero 1997) also been reported outside Australia.…”
Section: Introductionmentioning
confidence: 99%